The Expanded Core Curriculum Areas Experienced by Campers during Camp Abilities: A Qualitative Study . (January 2021) - Lieberman, Lauren J.; Ericson, Katie; Lepore-Stevens, Maria; Wolffe, Karen
Introduction: The expanded core curriculum (ECC) refers to the generally accepted nine areas of instruction that children who are visually impaired (i.e., those who are blind or have low vision) must learn through explicit instruction in order to live independently as adults. Children with visual impairments must experience immersion in the ECC in their daily lives throughout the year rather than only being taught these skills during the school year by teachers of students with visual impairments. Therefore, this research was undertaken to determine whether athletes attending Camp Abilities, a sports camp for children with visual impairments, experienced new ECC skills or practiced previously learned ECC skills and if so, how. Method: Researchers chose to interview 10 athletes from a purposeful sample of 30 children who had previously attended camp. The 10 coaches who worked with these athletes one-on-one participated in focus group discussions at the end of the weeklong camp. In addition, all athletes and coaches attending camp listed their thoughts on posters describing how all athletes attending experienced areas of the ECC. Finally, researchers documented observations of athletes' opportunities to practice ECC content throughout the weeklong program. Researchers transcribed interviews and focus group discussions and reviewed for themes relating to ECC areas that were part of the students' lived experience during camp. Results: Three major conclusions emerged from reviews of the interviews, discussion group transcripts, posters, and observations: (1) athletes and coaches were initially unclear about what the ECC areas were and how the athletes experienced the ECC in their everyday academic and home activities; (2) following clarification of the ECC areas, the athletes came to recognize how they learned and applied ECC skills during the camp experience; and (3) a more structured instructional approach to applying the ECC at camp may further enhance their experiences. Discussion: The youth participants were not able to list and describe all of the ECC areas when interviewed at the end of camp. However, adult participants (coaches) listed most ECC areas and described how athletes experienced the ECC during camp in their focus group discussions. Once researchers clarified ECC areas for athletes, they identified self-determination, recreation and leisure, social interaction, and independent living as the areas of the ECC most often experienced during camp. Implications for practitioners: Practitioners need to pay attention to structured learning of the ECC areas and consider articulating for students which areas overlap in their everyday lives, so that they are fully aware of the multiple skills they are acquiring. Camp Abilities is a functional way for youths with visual impairments to experience all areas of the ECC.